THE RELATIONSHIP OF JOB FATIGUE AND MENSTRUAL CYCLE IN SLEMAN POLICE POLICE WOMEN IN 2023 - Sukmawati, Rosnanda; Isnaeni, Isnaeni (HEARTY, 2024)
Background: The impact of continuous irregular menstrual cycles can cause reproductive system disorders which can be associated with an increased risk of various diseases such as ovarian cancer, breast cancer and infertility. In general, menstrual cycle disorders in women are caused by work fatigue for working women. Research Objective: To determine the relationship between work fatigue and the menstrual cycle of Sleman Police Women in 2023 Research Method: The research approach used in this research is cross-sectional. The population in this study was 100 policewomen from the Sleman Police. The sample required is 51 respondents. The sampling technique for respondents used a simple random sampling technique. The instrument in this research was to use a questionnaire. Researchers used the Chi Square test Research Results: The results of statistical tests show that the P value = 0.015 means p value < ∝ (0.05) so it can be concluded that there is a relationship between work fatigue and the menstrual cycle in Sleman Police Women in 2023. From the analysis results, the OR value is 5.333, meaning that work fatigue is mild 5.3 times more likely to experience regular menstrual cycles compared to heavy work fatigue. Conclusions and Suggestions: There is a relationship between work fatigue and the menstrual cycle in Sleman Police Women in 2023. It is hoped that the Sleman Police will take into account workers' rest time to minimize the occurrence of work fatigue so that they can increase work productivity.